SubFolderTrackingNo. WH50288A-WH50288C - Hanford Litigation Office Records (My University, 2016)
Records and evidence collected by the Hanford Litigation Office of Tom H. Foulds, Attorney at Law, over five decades. To access the digitized files, download .zip file, then click through the numbered folders until you see file extensions ending in .tif or a number sequence. Files with extensions such as .ntx, .dat, dbf, etc are artifacts from the original digitization process and can be ignored.

Files are presented as individual pages rather than multi-page documents. File names refer to document number then page number.
Files are presented as individual pages rather than multi-page documents. File names refer to document number then page number.